Transfusion‐related immunomodulation: gamma irradiation alters the effects of leukoreduction on alloimmunization. Issue 11 (13th October 2019) - Nelson, Karen A.; Aldea, Gabriel S.; Warner, Paul; Latchman, Yvette; Gunasekera, Devi; Tamir, Ayala; Gernsheimer, Terry; Bolgiano, Doug; Slichter, Sherrill J.
Abstract : BACKGROUND: Adverse events following blood transfusion include allosensitization and generalized immunosuppression, collectively referred to as transfusion‐related immune modulation. We evaluated the immunological effects of red blood cell (RBC) and platelet transfusions on alloantibody responses and on immunoregulatory cells in nonimmunosuppressed patients undergoing cardiovascular surgery. STUDY DESIGN AND METHODS: Patients were randomized to receive standard unmodified (STD), leukoreduced (LR), or leukoreduced and γ‐irradiated (LRγ) RBCs. Patients received only apheresis platelets that were in‐process LR and were γ‐irradiated for the third arm. Nontransfused patients served as controls for the effects of surgery itself on immunologic changes. Antibodies to HLA were assessed with use of solid‐phase assays. The effects of transfusion on adaptive and innate immunity were evaluated by assessing T regulatory cells (Tregs) and invariant natural killer T (iNKT) cells. RESULTS: LR of blood products reduced the development of human leukocyte antigen (HLA) alloantibodies, but only in patients without preexisting HLA antibodies. However, if LR blood products were γ‐irradiated, HLA antibody production was not reduced. Compared to nontransfused patients, recipients of STD or LR transfusions showed a significant increase in CD4+CD25 hi T cells expressing FoxP3 or CTLA4 and also of iNKT cells producing interleukin‐4. In contrast, recipients of LRγ blood products showed markedly lower increases in all three cellular assays. CONCLUSION: LR decreased HLA alloantibody production in naïve recipients, but did not reduce the immunosuppressive effects of transfusion. LRγ reduced immunosuppression and was not associated with decreased HLA alloantibody production.